Effects of Flexible Propulsors on Hydrodynamic Forces. Issue 21 (2019) - Shehata, Hisham M.; Hajj, Muhammad R.; Woolsey, Craig A.; Ragab, Saad
Abstract: We present experimental measurements of forward forces and external torques generated during forced oscillations of a tail on a fish-like body. The experiments were performed in a towing basin. Three panels having different flexural rigidity were tested over a range of oscillatory frequencies and leading edge amplitudes at 0 m/s and 0.35 m/s. The results show that tail panel flexibility enhances thrust production and thrust-to-input power ratios, with propulsive efficiencies reaching up to 45%.